A bio-based phosphaphenanthrene-containing derivative modified epoxy thermosets with good flame retardancy, high mechanical properties and transparency. Issue 49 (17th September 2021) - Peng, Wei; Xu, Yu-xuan; Nie, Shi-bin; Yang, Wei
Abstract : Phosphorus-containing flame retardants have received huge interest for improving the flame retardant behavior of epoxy resins (EP) over the past few decades. Abstract : Phosphorus-containing flame retardants have received huge interest for improving the flame retardant behavior of epoxy resins (EP) over the past few decades. However, a satisfactory flame retardant effect requires high loading of most phosphorus-containing flame retardants, resulting in the deterioration of the thermo-mechanical properties of the flame retardant epoxy materials. To obtain the flame retardant EP with excellent comprehensive properties, a furfurylamine-derived bis-DOPO derivative (FA-bis-DOPO) was synthesized from bio-mass as a co-curing agent for the flame retardant EP. The incorporation of FA-bis-DOPO improved the mechanical strength, the storage modulus and the glass transition temperature of the flame retardant epoxy materials, owing to its stiffness and reactivity with the epoxy matrix to enhance the crosslinking density. The EP material containing 5.0 wt% of FA-bis-DOPO had an LOI of 31.0% and UL-94 V-0 rating, while the pristine EP had an LOI of 23.5% and failed in the UL-94 test, manifesting the high flame retardant efficiency of FA-bis-DOPO. Besides, the cone calorimeter results demonstrated that the PHRR, THR, and TSP values of the EP/FA-bis-DOPO-5.0 were 28.0%, 27.3%, and 9.9% lower than those of the pristine EP, respectively. The flame retardant mechanism of FA-bis-DOPO could be attributed to the combined vapor and condensed phase mechanisms which involved the interruption of the combustion chain reaction by quenching radicals and the inhibition of the transfer of pyrolytic volatile products by catalytic formation of an intact and compact char layer.